The genus Ptiloneura (Psocodea: Ptiloneuridae) in Valle del Cauca, Colombia, altitudinal distribution, new records, and description of two species - González-Obando, Ranulfo; Aldrete, Alfonso N. García; Carrejo-Gironza, Nancy; Rodríguez, Valentina Sarria (Zootaxa, 2022)
From recent collections of psocids in natural areas of Valle del Cauca, Colombia, new records and two new species of the genus Ptiloneura were found. The latter are described and illustrated: P. elduende n. sp., and P. pichindensis n. sp., that correspond to a subclade previously named as genus Loneuroides. A map with the geographical and altitudinal distribution of the species in the department of Valle del Cauca, and a key for the determination of the species (males) in this subclade are presented.